Evolving Atomic Aesthetics and Dynamics - Davies, Edward; Tew, Phillip; Glowacki, David; Smith, Jim; Mitchell, Thomas (Evolutionary and Biologically Inspired Music, Sound, Art and Design, 2016)
The depiction of atoms and molecules in scientific literature owes as much to the creative imagination of scientists as it does to scientific theory and experimentation. danceroom Spectroscopy (dS) is an interactive art/science project that explores this aesthetic dimension of scientific imagery, presenting a rigorous atomic simulation as an immersive and interactive installation. This paper introduces new methods based on interactive evolutionary computation which allow users - both individually and collaboratively - to explore the design space of dS and construct aesthetically engaging visual states. Pilot studies are presented in which the feasibility of this evolutionary approach is discussed and compared with the standard interface to the dS system. Still images of the resulting visual states are also included.